Formulation of mortars with nano-SiO2 and nano-TiO2 for degradation of pollutants in buildings - Senff, L.
This paper reports on the design of cement mortars that use nano-SiO2 (nS) and nano-TiO2 (nT) particles, aiming to improve the durability of traditional building materials while giving new functionalities (aerial decontamination of pollutants). Samples with 0-2 wt.% nS, 0-20 wt.% nT, 0.45-7 wt.% superplasticizer (SP) and 0.45-0.58 water/binder weight ratio were prepared. The formulations of mortars were defined according to rheology and flow table measurements, then showing suitable workability. The temperature of hydration, compressive strength, water absorption, and photocatalytic degradation of pollutants (NOx and Orange II dye) were also evaluated. In general, the rheological behavior and the temperature of hydration changed in distinct levels, depending on the dosage and type of nanoadditives, but nT influenced more significantly the results. However, such differences were not identified on the compressive strength and water absorption. In addition, NOx photocatalytic degradation up to 1 h under solar light ranged from 65% to 80%, while Orange II degradation after 9 h under visible light changed from 18% to 50%. (C) 2012 Elsevier Ltd. All rights reserved.